Influence of nano-SiO2 and carbonation on the performance of natural hydraulic lime mortars. (28th February 2020) - Luo, Kai; Li, Jun; Han, Qing; Lu, Zhongyuan; Deng, Xin; Hou, Li; Niu, Yunhui; Jiang, Jun; Xu, Xiaoying; Cai, Pan
Highlights: In NHL2 mortars carbonation percentage would increase with the increased NS. NS doped NHL2 mortars can capture and utilize much more CO2. The capture and solidification of CO2 could also improve the mechanical properties. NS and accelerated carbonation curing can reduce the pore diameter of NHL2 mortars. Abstract: As an ideal cementitious material for the maintenance of historic buildings and the replacement of interior decoration mortars, the widespread application of natural hydraulic lime (NHL) is expected to play an important role in CO2 capture and utilization. Structures and properties of NHL2 mortars with nano-SiO2 (NS) under carbonation were researched in this paper. NHL mortars could capture CO2 during hardening process of air-hardening contents, and the captured CO2 would be fixed in the matrix to form CaCO3 . Carbonation percentage and extent of NHL2 mortars increased by the addition of NS whatever in atmospheric or accelerated carbonation condition. Much more compacted carbonation surfaces than that of the uncarbonated region for NHL2 mortars with NS was observed. The addition of NS will reduce the porosity and big pores (approximately 1 μm) while increase the mesopores (approximately 50 nm) of the mortars. Carbonation reaction of NHL2 mortars seemed to be improved by the addition of NS, which would be beneficial to the collection, solidification and further utilization of CO2 .